Stretchable Conductive Ink Using Copper Fillers - Wahid, Wan Azrina Mohd (Universiti Sains Malaysia, 2017)
This research focused on the stretchable conductive ink using copper fillers. Nowadays, a lot of application which involves stretchable conductive ink using silver fillers. The silver fillers are one of the common and popular conductive ink. However, due to its high cost, it limits the usage in the wider application. Copper fillers have the comparable conductivity with silver fillers. So, the copper fillers have been chosen as conductive fillers in this project. Some modification needed due to copper fillers tendency to oxidise in the ambient environment. Incorporation of silver fillers is a method to enhance the conductivity of stretchable conductive ink using copper fillers. The stretchable conductive ink using copper fillers are characterised by UV-visible transmittance, XRD, SEM and tensile testing. To study the thermal properties, DSC and TGA are conducted. The conductivity of stretchable conductive ink is measured by a multimeter. It found that conductivity of stretchable conductive ink increasing when increasing copper fillers but the higher tendency also for the copper filler to oxidise and reduce conductivity.